A qualitative analysis of the effect of wholistic-analytic cognitive style dimension on the cultural heritage game playing - Raptis, George E.; Fidas, Christos; Avouris, Nikolaos (2016 7th International Conference on Information, Intelligence, Systems & Applications (IISA), 2016)
Retrieving, recalling, processing, organising and storing information are integral parts of the human information seeking process and many socio-cognitive theories suggest that the approach of the seekers is closely related to their cognitive processing styles and abilities. The aim of this study is to investigate the impact of wholistic-analytic cognitive style to players' behaviour in the context of a cultural heritage game. Thirty two people participated in the study and qualitative data were collected and analysed in order to study the aforementioned effects. Analysis of results revealed differences in behavioural patterns between wholists and analysts. Findings of this study are expected to be used by game designers and practitioners aiming to offer bootstrapped gaming experiences based on individual differences in information processing.